The myth of political correctness the conservative attack on higher education - Wilson, John K. 1969- (Duke University Press, 1995)
1. The Myth of Political Correctness -- 2. Conservative Correctness -- 3. The Cult of Western Culture -- 4. The Myth of Speech Codes -- 5. The Myth of Sexual Correctness -- 6. The Myth of Reverse Discrimination -- Conclusion: Beyond Political Correctness